Sorption of ions Cu(II), Cd(II), Co(II), Zn(II), and Cr(VI) by a composite sorbent on the base of nano-sized iron - Kovalchuk, I.A.; Pylypenko, I.V.; Tobilko, V.Yu.; Kornilovych, B.Yu. (Reports of the National Academy of Sciences of Ukraine, 2021)
The features of the sorption extraction of heavy metals (Cu (II), Cd (II), Zn (II), Co (II), Cr (VI)) from complex waste water contents containing a mixture of these ions by a composite based on nano-sized iron with the use, as an inorganic matrix, a highly active dispersed mineral montmorillonite are investigated. The dependences of the sorption values of heavy metals on pH are obtained. Sorption processes are quantitatively described using the surface complexation models (diffuse double layer model (DDLM)). It is found that the selectivities of cations of heavy metals form a series: Cu > Zn > Co > Cd, which is characteristic of both pure montmorillonite and the composite sorbent. It is found that the obtained composite material has significantly better sorption properties for the extraction of heavy metals from aqueous solutions compared to natural montmorillonite. The analysis of sorption isotherms is performed using the Langmuir and Freundlich equations. High sorption characteristics of the composite sorbent based on nano-sized zero-valent iron and dispersed montmorillonite silicate relative to heavy metal copper, cadmium, zinc, cobalt, and chromium determine the prospects of its use in the treatment of multicomponent waste water from galvanic industries and hydrometallurgical enterprises.